2009
DOI: 10.1038/nrmicro2185
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the machine: adaptor proteins for Hsp100/Clp and AAA+ proteases

Abstract: Members of the AAA+ protein superfamily contribute to many diverse aspects of protein homeostasis in prokaryotic cells. As a fundamental component of numerous proteolytic machines in bacteria, AAA+ proteins play a crucial part not only in general protein quality control but also in the regulation of developmental programmes, through the controlled turnover of key proteins such as transcription factors. To manage these many, varied tasks, Hsp100/Clp and AAA+ proteases use specific adaptor proteins to enhance or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
251
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(253 citation statements)
references
References 162 publications
2
251
0
Order By: Relevance
“…ClpP is a serine protease consisting of two stacked heptameric rings with a small central entrance pore, and forms a complex with ClpATPases named ClpAP or ClpXP. Under physiological conditions, ClpP has only limited activity to degrade small peptides on its own, and mostly functions as a complex with ClpATPases (Kirstein et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…ClpP is a serine protease consisting of two stacked heptameric rings with a small central entrance pore, and forms a complex with ClpATPases named ClpAP or ClpXP. Under physiological conditions, ClpP has only limited activity to degrade small peptides on its own, and mostly functions as a complex with ClpATPases (Kirstein et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In some cases, however, degron recognition requires an adaptor protein, which couples substrate recognition and delivery ( Fig. 1), by interacting with both the substrate and the AAA1 protease (8,(18)(19)(20). In these cases, a second element within the substrate may be required for its engagement with the translocation pore of the AAA1 protease (21).…”
Section: Controlled Protein Degradation By Bacterial Aaa1 Proteasesmentioning
confidence: 99%
“…A number of stress response pathways are controlled by proteolysis (8,30,39,68) and this is also true for the mitochondrial unfolded protein response, at least in C. elegans. By performing genome wide RNAi screens in the nematode worm C. elegans, Ron and coworkers found that ClpP, a subunit of the AAA1 protease, as well as four other proteins HAF-1, DVE-1, UBL-5, and ZC376.7 were necessary for signaling the mitochondrial UPR (62,64,69,70).…”
Section: Proteolytic Control Of the Mitochondrial Unfolded Protein Rementioning
confidence: 99%
See 1 more Smart Citation
“…For example, in B. subtilis and Streptococcus thermophilus, MecA acts as an adaptor protein for ClpC, and is required for hexamerization and complex formation with ClpP (Boutry et al, 2012;Mei et al, 2009;Wang et al, 2011). The substrates and the adaptor proteins for ClpEP-mediated degradation are unknown, and the exact role of ClpEP in protein quality control remains to be explored (Kirstein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%